If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4.8 + 7(1.2 + -3(36)) = 3(1.2 + -7(36)) Multiply -3 * 36 -4.8 + 7(1.2 + -108) = 3(1.2 + -7(36)) Combine like terms: 1.2 + -108 = -106.8 -4.8 + 7(-106.8) = 3(1.2 + -7(36)) Multiply 7 * -106.8 -4.8 + -747.6 = 3(1.2 + -7(36)) Combine like terms: -4.8 + -747.6 = -752.4 -752.4 = 3(1.2 + -7(36)) Multiply -7 * 36 -752.4 = 3(1.2 + -252) Combine like terms: 1.2 + -252 = -250.8 -752.4 = 3(-250.8) Multiply 3 * -250.8 -752.4 = -752.4 Add '752.4' to each side of the equation. -752.4 + 752.4 = -752.4 + 752.4 Combine like terms: -752.4 + 752.4 = 0.0 0.0 = -752.4 + 752.4 Combine like terms: -752.4 + 752.4 = 0.0 0.0 = 0.0 Solving 0.0 = 0.0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4x+(x+3)+2(x+4)= | | ln(x)/ln(y) | | -4.8+7(1-3(25))=3(1-7(25)) | | (x-0.5)(x-0.5)+1.561=0 | | 2p^2x^2+pqx-15q^2=0 | | 5x-8=28-4x | | 5x-8=28-4 | | 56a(3+x-2b)=c(dx-2) | | x^4-6x^3+27x=0 | | (6n^4-2n+5n)+(2n+6n^4+4n^2)= | | .96+x=.16(12+x) | | 41x^2=9 | | B+x=18 | | 9x-8=5x+24 | | 2(x^3-5x^2+11x)=2x^3-5(2x^2+4x)+165 | | 15w-4(3w-1)=19 | | 15x-12=-12 | | 15x-12=-27 | | 4x+2x-42=-x-12+10x-6 | | N=323-192 | | 5x^2-13x=30 | | -8x/2 | | -7n+21=1-2n | | 4x+11y=4.6 | | X^2-12x=-72 | | 14-3(5t-12)=1-20+1 | | -4x+3(-2x+6)=8 | | 5x^2+2x+11= | | m+n+p=11 | | (y+3)+2y=(9y+6)-8 | | 5x+47=57 | | 5x(x-1)=2(1-x) |